US Global Food Security Strategy (GFSS) Baseline Survey, 2018-2019 - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
The purpose of the US Global Food Security Strategy (GFSS) 2018/2019 baseline survey in Bangladesh is to provide the U.S. Government interagency partners, the United States Agency for International Development (USAID) Bureau for Resilience and Food Security (RFS), USAID/Bangladesh, the Government of Bangladesh, and development partners with information on the current status of the Feed the Future Zone of Influence (ZOI)-level population-based survey indicators. The survey is designed to establish the current status of Feed the Future indicators in the ZOI for the second phase of Feed the Future, also known as GFSS. For more information on the US GFSS Bangladesh Country Plan, please visit this link. Upon request from USAID, IFPRI designed and conducted the US Global Food Security Strategy (GFSS) 2018/2019 baseline survey, which was implemented in the field from November 11, 2018 to February 6, 2019. The GFSS 2018/2019 baseline survey covers mostly rural areas in the south and southwest region of the country. In addition to the 20 districts in three divisions that create the Feed the Future sample, the GFSS sample added Kushtia district in Khulna division based on its poverty and stunting trends. The 21 districts making up the GFSS are listed below: 1. Barishal division (six districts): Barguna, Barishal, Bhola, Jhalakati, Patuakhali, and Pirojpur; 2. Dhaka division (five districts): Faridpur, Gopalganj, Madaripur, Rajbari, and Shariatpur; and 3. Khulna division (10 districts): Bagerhat, Chuadanga, Jashore, Jhenaidah, Khulna, Kushtia, Magura, Meherpur, Narail, and Satkhira. The GFSS sample includes 2,525 households in 125 primary sampling units (that is, villages). The GFSS sample design followed a stratified sampling in two stages: (1) randomly selected 125 PSUs (villages) with probability proportional to size (PPS) sampling using the number of households in each village as the size, and (2) after a complete census in each of the selected villages was conducted, randomly selected 20 households per PSU from the census list—using the sampling frame developed from the community series of the 2001 population census of Bangladesh.